Wages in Singapore - Gan, Benjamin Thiam Soon (2015)
In all manufacturing industries, wages constitute a substantial proportion of cost. If not properly controlled, it would affect the competitiveness of the firm and even industry. This project hopes to provide a clearer idea of the wage structure in Singapore. Firstly, a history of Singapore's experience through the late 60s, 70s, 80s and early 90s, her policies on wages and labour shortage through the 80s and 90s. This is followed by a literature review of important theories and models relevant to this topic, like the competitive wage theories. Next, the reader will be presented with the analysis first from the macro perspective, i.e. across a period of time and across sectors. Time series is used to capture important data and identify trend in relation to external factors like government, economic situations in Singapore and around the world. 3-digit manufacturing industries analysis is conducted to observed the trend over a 15 year period. Inter-sectoral data is also presented for comparison. Subsequently, there will be an analysis of the various components that affect wages like value added per worker, capital intensity using regression analysis. This is the first time that this topic has been researched outside government departments. However, it has been limited on many occasions due to the lack of data. Efforts put in to collect data from government departments have met with failure, this was especially so with Ministry of Labour. They were unwilling to provide any extra data except those already published.